Komitmen Pelayanan Penatua Dan Syamas Dan Pekerjaan Sekuler - Maindoka, Deisy Jelfie (Educatio Christi, 2020)
The Special Servant at GMIM is an ecclesiastical position whose vocation begins with the election, then is followed by self-determination, confirmation and giving. This election is believed to be an action or an effort by the church to realize the pattern of ministry and g overnment of Christ (christocracy) by selecting certain people. Special servants have a big service responsibility, which is to give themselves fully in service as a form of response to God's call as a serving leader. Service commitment is needed in the service of elders and shamas and to balance the secular work that has been undertaken so far. Special servants as wise persons know how to divide their time between ministry and daily work.